Increasing Understanding of the Islamic Religion Through Interactive Methods for Children with Special Needs - Mirrota, Dita Dzata; Hasan, Moch. Sya'roni; Ainiyah, Qurrotul (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This study aims to design and implement interactive learning methods in Islamic Religious Education (PAI) subjects, in particular, intellectual disability (tuna daksa) classes at SMA LK As Shofa Mojokerto, as well as analyze the effectiveness of these methods in improving students' understanding of PAI subject matter. The interactive methods applied include group discussions, role-playing, and demonstrations. The study employs a qualitative approach with a case study design. The research subjects are PAI teachers and students in a particular tuna daksa class at the high school. Data is collected through interviews, observations, and documentation studies. The results show that the application of interactive learning methods can improve intellectually disabled students' understanding of Islamic religious subject matter. Students have become more active and enthusiastic in PAI learning activities. They also find it easier to understand the material through direct activities and role-playing so that their religious learning outcomes improve. This study contributes to the development of innovative and contextual PAI learning methods for students with intellectual disabilities in inclusive schools.